THE PROVINCES (HUNGARIAN VIDÉK) IN CHOSEN HUNGARIAN FEATURE FILMS. SOCIAL, POLITICAL AND HISTORICAL ASPECTS - Bubak, Grzegorz (Porównania, 2012)
Analyzing the occurrence of the so-called countryside in the Hungarian films, one can see several variants of this problem. This is the place from which main character escapes, moves to the big city to change his live. Some of individuals deliberately disunite family ties and old contacts, to completely cut off from their roots. Others will remember with fondness their childhood. There are also movies where the story takes place exclusively in the countryside, then the viewer follows the characteristic rituals and customs of the scenery. It is not always the countryside shown directly, sometimes only as a reference point, a memory, but also a way of thinking and behaving as well.